A method for designing the proportion of ultra-high toughness cement-based composite materials and analyzing their performance
Through multi-dimensional multi-index index evaluation and performance test, the optimal ratio of cement matrix composite materials was screened out, which solved the problem of single evaluation indicators and lack of experimental verification in the existing technology, and improved the reliability and optimization capabilities of proportion analysis.
Patent Information
- Application Number
- CN202510039849.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing cement matrix composite ratio design and performance analysis methods have limitations in practical applications, including a single evaluation index, a lack of productivity tests and performance tests, and an under-utilization of analysis results to optimize proportions.
A combination design and performance analysis method for ultra-high toughness cement matrix composite materials is proposed. By obtaining the preliminary proportion range, designing the trial assembly plan, conducting performance test of the trial assembly plan, screening the recommended trial assembly plan, and analyzing the relationship model between proportion and performance.
The reliability of the optimal proportion analysis results of cement matrix composite materials is improved, and better proportions are screened through multi-dimensional and multiple index evaluations, and a relationship model is provided for subsequent optimization.
Smart Images

Figure CN119446371B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of cement-based composite material ratio analysis, and relates to a method for ratio design and performance analysis of an ultra-high toughness cement-based composite material. Background Art
[0002] Cement-based composite materials are multiphase material systems that use cement as the main binder and are mixed with other mineral admixtures, aggregates, fibers and additives in a certain proportion. They are widely used in the fields of construction engineering and industry.
[0003] The ratio of cement-based composite materials directly determines their strength characteristics and also affects their resistance to environmental erosion factors. By accurately designing and analyzing the ratio of cement-based composite materials and testing their related properties, materials with suitable mechanical properties, durability and working performance can be customized according to specific engineering needs, which helps to avoid engineering accidents caused by material quality problems, reduce maintenance and reconstruction costs, and ensure safety, which is of practical significance.
[0004] However, the existing cement-based composite material mix design and performance analysis methods still have some limitations and shortcomings in practical applications.
[0005] For example, an existing Chinese patent with publication number CN119066860A discloses a design method for hydraulic high-ductility cement-based composite materials based on crack width and ultimate elongation control, the method comprising: constructing a crack width model and an ultimate elongation model; determining the simulated crack width of each crack generated during the tensile load test simulation according to the pending design scheme and the crack width model; determining the simulated ultimate elongation according to the pending design scheme and the ultimate elongation model; adjusting the pending design scheme based on the simulated crack width and the simulated ultimate elongation. By constructing a crack width model and an ultimate elongation model, the application can improve the efficiency and rationality of the design of hydraulic high-ductility cement-based composite materials.
[0006] The above patent has the following shortcomings: First, it evaluates and adjusts the pending design scheme and obtains the optimal ratio of cement-based composite materials based only on the two indicators of crack width and elongation. The evaluation indicators are relatively single and not diverse enough, which in turn affects the reliability of the analysis results of the optimal ratio of cement-based composite materials.
[0007] Secondly, the effects of the proposed design schemes were predicted and adjusted based on the simulation model, but no production tests and performance tests were conducted. As a result, there may be certain errors in the evaluation results, which is not conducive to screening out the optimal ratio of cement-based composite materials.
[0008] Thirdly, in the process of adjusting the pending design scheme and obtaining the optimal ratio of cement-based composite materials, the analysis results were not fully utilized, such as obtaining the relationship between the ratio change and performance of cement-based composite materials, which was not conducive to the subsequent targeted optimization of the ratio of cement-based composite materials. Summary of the invention
[0009] In view of the above problems, the present invention proposes a method for proportion design and performance analysis of ultra-high toughness cement-based composite materials. The specific technical scheme is as follows: A method for proportion design and performance analysis of ultra-high toughness cement-based composite materials, comprising the following steps: Step 1, obtaining a preliminary proportion range: obtaining engineering requirement information of the target project, wherein the engineering requirement information includes strength grade, durability requirement information, workability requirement information, and special performance requirement information, and analyzing the preliminary proportion range of the water-cement ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in cement-based composite materials.
[0010] Step 2. Design trial mix schemes: According to the preliminary ratio ranges of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials, adjust and set the values of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials to obtain various trial mix schemes for cement-based composite materials.
[0011] Step 3, performance test of trial mix schemes: obtain samples of cement-based composite materials of various trial mix schemes of cement-based composite materials, record them as samples of various trial mix schemes, conduct workability test, mechanical property test, durability test, microstructure analysis test on the samples of various trial mix schemes, and analyze the evaluation coefficients of workability, mechanical property, durability, and microstructure of various trial mix schemes.
[0012] Step 4: Screening of recommended trial mix solutions: Based on the evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial mix solutions, screen the recommended trial mix solutions and provide feedback.
[0013] Step 5. Analysis of the relationship between mix ratio and performance: Analyze the relationship model between the workability, mechanical properties, durability, microstructure and water-cement ratio, cementitious material-aggregate ratio, and fiber-matrix ratio of cement-based composite materials, and provide feedback.
[0014] Compared with the prior art, the method for proportion design and performance analysis of ultra-high toughness cement-based composite materials described in the present invention has the following beneficial effects: 1. The present invention evaluates the recommended trial mix of cement-based composite materials based on multiple indicators in multiple dimensions of workability, mechanical properties, durability, and microstructure, thereby improving the reliability of the analysis results of the best proportion of cement-based composite materials.
[0015] 2. The present invention conducts workability tests, mechanical property tests, durability tests, and microstructure analysis tests on production samples corresponding to various trial mixing schemes of cement-based composite materials, and conducts a comprehensive reliability evaluation of various trial mixing schemes, which is conducive to better screening out the optimal ratio of cement-based composite materials.
[0016] 3. The present invention analyzes the relationship model between the workability, mechanical properties, durability, microstructure and water-cement ratio, cementitious material and aggregate ratio, and fiber and matrix ratio of cement-based composite materials, which is conducive to the subsequent targeted optimization of the proportion of cement-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0018] Figure 1 It is a schematic diagram of the method flow of the present invention.
[0019] Figure 2 This is an analysis flow chart of step one of the present invention.
[0020] Figure 3 It is the analysis flow chart of step 4 of the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] See also Figure 1 As shown, the present invention provides a method for proportion design and performance analysis of ultra-high toughness cement-based composite materials, comprising the following steps: Step 1, obtaining a preliminary proportion range: obtaining engineering requirement information of a target project, wherein the engineering requirement information includes strength grade, durability requirement information, workability requirement information, and special performance requirement information, and analyzing the preliminary proportion ranges of the water-cement ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in cement-based composite materials.
[0023] As a preferred option, see Figure 2As shown, the specific analysis process of step 1 includes: obtaining the engineering requirement information of the target project, obtaining the strength grade, durability requirement information, workability requirement information, and special performance requirement information of the target project, and further obtaining the values of various indicators of the durability requirement, workability requirement, and special performance requirement of the target project, which are recorded as , Indicates durability requirements The number of the indicator, , Indicates work requirements The number of the indicator, , Indicates special performance requirements The number of the indicator, .
[0024] It should be noted that the engineering requirements of the target project are set according to actual application needs.
[0025] It should be noted that the strength grade refers to the concrete strength grade, including but not limited to C30, C40, etc.
[0026] It should be noted that the durability requirements refer to the durability requirements of concrete, and the various indicators of durability requirements include but are not limited to impermeability, frost resistance, erosion resistance, etc.
[0027] It should be noted that the workability requirements refer to the workability requirements of concrete. The various indicators of the workability requirements include but are not limited to slump, expansion, cohesion, water retention, etc.
[0028] It should be noted that the special performance requirements refer to the special performance requirements of concrete. The various indicators of special performance requirements include but are not limited to crack resistance, impact resistance, thermal insulation, radiation resistance, etc.
[0029] The water-binder ratio, cementitious material-aggregate ratio, fiber-matrix ratio and engineering requirement information corresponding to various engineering conditions stored in the database are extracted.
[0030] It should be noted that the ratio ranges of water-cement ratio, cementitious material-aggregate ratio, and fiber-matrix ratio in cement-based composite materials under various engineering conditions stored in the database are obtained by referring to relevant technical data, research reports, engineering practice experience or relevant industry specifications and standards.
[0031] According to the engineering requirement information corresponding to various engineering conditions, the strength grades corresponding to various engineering conditions and the values of various indicators of durability requirements, workability requirements, and special performance requirements are obtained, and the values of various indicators of durability requirements, workability requirements, and special performance requirements corresponding to various engineering conditions are recorded as , Indicates The number of the engineering condition, .
[0032] As a preferred solution, the specific analysis process of step 1 further includes: respectively setting strength level matching factors corresponding to the same and different strength levels, comparing the strength levels corresponding to various engineering conditions with the strength level of the target project, and obtaining the strength level matching factors of various engineering conditions and the target project, which are recorded as .
[0033] The values of the durability requirements, workability requirements, and special performance requirements corresponding to various engineering conditions are compared with the values of the durability requirements, workability requirements, and special performance requirements of the target project, and the deviations of the durability requirements, workability requirements, and special performance requirements between various engineering conditions and the target project are obtained, which are recorded as .
[0034] It should be noted that the deviation of an indicator refers to the absolute value of the difference between the indicator values.
[0035] By analyzing the formula Obtain the durability matching factor between various engineering conditions and the target project , Indicates the number of engineering conditions.
[0036] Similarly, according to the analysis method of durability matching factors between various engineering conditions and target projects, the workability matching factors and special performance matching factors between various engineering conditions and target projects are obtained and recorded as .
[0037] By analyzing the formula Get the matching index of various engineering conditions and target engineering ,in Indicates the correction factor of the preset fit index, Represents a natural constant.
[0038] It should be noted that the correction coefficient of the matching index plays a role in amplifying, reducing or rounding the matching index to facilitate calculation and analysis.
[0039] The matching indexes of various engineering conditions and the target project are compared with each other, and the engineering conditions corresponding to the maximum matching index are recorded as similar engineering conditions. The ratio ranges of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials under similar engineering conditions are obtained and recorded as the preliminary ratio ranges of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials.
[0040] In a specific embodiment, the preliminary ratio range of water-binder ratio in the cement-based composite material is 0.2-0.35, the preliminary ratio range of cementitious material to aggregate ratio is 1:1-1:3, and the preliminary ratio range of fiber to matrix ratio is 0.5%-2.0%.
[0041] It should be noted that the type of fiber in the cement-based composite material can be PVA fiber, steel fiber, carbon fiber, etc.
[0042] Step 2. Design trial mix schemes: According to the preliminary ratio ranges of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials, adjust and set the values of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials to obtain various trial mix schemes for cement-based composite materials.
[0043] As a preferred solution, the specific analysis process of step 2 is: according to the preliminary ratio range of water-binder ratio, ratio of cementitious material to aggregate, and ratio of fiber to matrix in cement-based composite materials, select each value in the preliminary ratio range of water-binder ratio, ratio of cementitious material to aggregate, and ratio of fiber to matrix in cement-based composite materials according to the preset equal interval principle, and obtain each reference value of water-binder ratio, ratio of cementitious material to aggregate, and ratio of fiber to matrix in cement-based composite materials.
[0044] According to the preset principles, various reference values of water-cement ratio, various reference values of cementitious material-aggregate ratio, and various reference values of fiber-matrix ratio in cement-based composite materials are combined to obtain various trial mixing schemes of cement-based composite materials.
[0045] It should be noted that each trial mix corresponds to a set of cement-based composite material ratio data, that is, each trial mix has its corresponding water-cement ratio, cementitious material-aggregate ratio, and fiber-matrix ratio.
[0046] It should be noted that different trial mix schemes use different water-cement ratios, cementitious material-aggregate ratios, and fiber-matrix ratios for trial mix.
[0047] It should be noted that when designing a trial mix of cement-based composite materials, the trial mix should have a certain degree of representativeness and coverage so as to fully understand the effects of the water-cement ratio, the ratio of cementitious materials to aggregates, and the ratio of fibers to matrix in cement-based composite materials on the performance of cement-based composite materials.
[0048] Step 3, performance test of trial mix schemes: obtain samples of cement-based composite materials of various trial mix schemes of cement-based composite materials, record them as samples of various trial mix schemes, conduct workability test, mechanical property test, durability test, microstructure analysis test on the samples of various trial mix schemes, and analyze the evaluation coefficients of workability, mechanical property, durability, and microstructure of various trial mix schemes.
[0049] As a preferred solution, the specific analysis process of step 3 includes: extracting a set number of samples from each sample of various trial mixes to perform workability tests, wherein the workability tests include slump tests and expansion tests, obtaining the slump and expansion of the samples corresponding to the various trial mixes, and recording them as , Indicates The number of the trial combination, .
[0050] It should be noted that all samples of the same test solution are completely consistent.
[0051] It should be noted that the workability test of the samples of the trial mix is carried out during the stirring and mixing stage of the samples.
[0052] It should be noted that the slump test and expansion test on cement-based composite material samples are relatively common technical means, and the specific operation process will not be described here.
[0053] In a specific embodiment, two samples are taken from each sample of various trial mixes for workability test, wherein the first sample is subjected to slump test and the second sample is subjected to expansion test, and the slump of the first sample is used as the slump of the sample corresponding to the trial mix, and the expansion of the second sample is used as the expansion of the sample corresponding to the trial mix.
[0054] By analyzing the formula Obtain the workability evaluation coefficients of various trial solutions ,in Represents the correction factor of the preset workability evaluation coefficient, Respectively represent the preset slump and spread thresholds, Respectively represent the weights of the preset slump and spread, .
[0055] It should be noted that the correction factor of the workability evaluation coefficient plays the role of amplifying, reducing or rounding the workability evaluation coefficient to facilitate calculation and analysis.
[0056] It should be noted that the weights of the slump and spread are set according to their importance in evaluating workability. In a specific embodiment, the weights of the slump and spread are 0.5 and 0.5 respectively.
[0057] It should be noted that slump is an indicator to measure the fluidity of cement-based composite materials. The larger the slump, the stronger the ability of concrete to flow under its own weight, which means that its workability is better.
[0058] It should be noted that the expansion degree is a further measure of the ability of cement-based composite materials to flow and expand in the horizontal direction based on the slump test. The greater the expansion degree, the better the fluidity of the concrete and the better the workability.
[0059] As a preferred solution, the specific analysis process of step 3 further includes: extracting a set number of samples from each sample of various trial matching schemes to perform mechanical property tests, wherein the mechanical property tests include compressive strength tests, tensile strength tests, and flexural strength tests, and obtaining the compressive strength, tensile strength, and flexural strength of the samples corresponding to the various trial matching schemes under the set load, and recording them as .
[0060] It should be noted that the mechanical properties test of the samples of the trial mix is carried out at the stage when the samples are made into test pieces.
[0061] It should be noted that the compressive strength test, tensile strength test and flexural strength test of cement-based composite material samples are relatively common technical means, and the specific operation process is not described here. Among them, the loads and loading rates applied in the compressive strength test, tensile strength test and flexural strength test are all set values.
[0062] In a specific embodiment, three samples are taken from each sample of various trial preparation schemes for mechanical property tests, wherein the first sample is subjected to a compressive strength test, the second sample is subjected to a tensile strength test, and the third sample is subjected to a flexural strength test, and the compressive strength of the specimen made from the first sample is used as the compressive strength of the sample corresponding to the trial preparation scheme under a set load, the tensile strength of the specimen made from the second sample is used as the tensile strength of the sample corresponding to the trial preparation scheme under a set load, and the flexural strength of the specimen made from the third sample is used as the flexural strength of the sample corresponding to the trial preparation scheme under a set load.
[0063] By analyzing the formula Obtain the mechanical properties evaluation coefficients of various trial matching schemes ,in Indicates the correction factor of the preset mechanical property evaluation coefficient, Respectively represent the preset thresholds of compressive strength, tensile strength, and flexural strength, Respectively represent the weights of the preset compressive strength, tensile strength, and flexural strength, .
[0064] It should be noted that the correction factor of the mechanical property evaluation coefficient plays the role of amplifying, reducing or rounding the mechanical property evaluation coefficient to facilitate calculation and analysis.
[0065] It should be noted that the weights of the compressive strength, tensile strength and flexural strength are set according to their importance in evaluating mechanical properties. In a specific embodiment, the weights of the compressive strength, tensile strength and flexural strength are 0.3, 0.35 and 0.35 respectively.
[0066] It should be noted that the greater the compressive strength, the greater the tensile strength, and the greater the flexural strength, the better the mechanical properties.
[0067] As a preferred solution, the specific analysis process of step 3 further includes: extracting a set number of samples from each sample of various trial solutions for durability test, wherein the durability test includes an impermeability test and a frost resistance test, obtaining the impermeability coefficient and frost resistance coefficient of the samples corresponding to various trial solutions under the set test conditions, and recording them as .
[0068] It should be noted that the durability test of the samples of the trial mix is carried out at the stage when the samples are made into test pieces.
[0069] It should be noted that the permeability test and frost resistance test of cement-based composite material samples are relatively common technical means, and the specific operation process is not described here. Among them, the permeability test uses a permeameter to test the water seepage depth of the cement-based composite material specimen under the set water pressure, and substitutes the preset relationship function between the water seepage depth and the permeability coefficient to obtain the permeability coefficient of the cement-based composite material specimen; the frost resistance test tests the mass loss and relative dynamic modulus of the cement-based composite material specimen under the set freeze-thaw temperature, freeze-thaw time and freeze-thaw cycle number, and substitutes it into the preset relationship function between the mass loss, relative dynamic modulus and the frost resistance coefficient to obtain the frost resistance coefficient of the cement-based composite material specimen.
[0070] In a specific embodiment, two samples are taken from each sample of various trial mixing schemes for durability testing, wherein the first sample is subjected to an impermeability test, and the second sample is subjected to a frost resistance test, and the impermeability coefficient of the specimen made from the first sample is used as the impermeability coefficient of the sample corresponding to the trial mixing scheme under the set test conditions, and the frost resistance coefficient of the specimen made from the second sample is used as the frost resistance coefficient of the sample corresponding to the trial mixing scheme under the set test conditions.
[0071] By analyzing the formula Obtain the durability evaluation coefficient of various trial solutions ,in Indicates the correction factor of the preset durability evaluation coefficient, Respectively represent the thresholds of the preset anti-permeability coefficient and anti-freezing coefficient, Respectively represent the weights of the preset anti-permeability coefficient and anti-freezing coefficient, .
[0072] It should be noted that the correction factor of the durability evaluation coefficient plays the role of amplifying, reducing or rounding the durability evaluation coefficient to facilitate calculation and analysis.
[0073] It should be noted that the weights of the impermeability coefficient and the frost resistance coefficient are set according to their importance in evaluating durability. In a specific embodiment, the weights of the impermeability coefficient and the frost resistance coefficient are 0.5 and 0.5 respectively.
[0074] It should be noted that the greater the impermeability coefficient and the frost resistance coefficient, the better the durability.
[0075] As a preferred embodiment, the specific analysis process of step 3 further includes: extracting a set number of samples from each sample of various trial mixing schemes for microstructure analysis test, obtaining pore structure information and microcrack information of the samples corresponding to the various trial mixing schemes, wherein the pore structure information includes porosity and average pore size, and the microcrack information includes the number of microcracks, the width of microcracks, and the growth rate of microcracks, and the porosity, average pore size, number of microcracks, width of microcracks, and growth rate of microcracks of the samples corresponding to the various trial mixing schemes are recorded as .
[0076] It should be noted that the microstructure analysis test of the samples of the trial mix is carried out during the hardening stage of the samples.
[0077] It should be noted that microstructural analysis of cement-based composite material samples is a relatively common technical means currently available, and its specific operation process will not be described in detail here.
[0078] In a specific embodiment, a sample is randomly selected from each sample of various trial preparation schemes for microstructure analysis test, and the pore structure information and microcrack information of the sample after hardening are used as the pore structure information and microcrack information of the sample corresponding to the trial preparation scheme.
[0079] By analyzing the formula Get the microstructure evaluation coefficient of various trial solutions ,in represents the correction factor of the preset microstructure evaluation coefficient, They respectively represent the preset thresholds of porosity, average pore size, number of microcracks, width of microcracks, and microcrack expansion speed.
[0080] It should be noted that the correction factor of the microstructure evaluation coefficient plays the role of amplifying, reducing or rounding the microstructure evaluation coefficient to facilitate calculation and analysis.
[0081] It should be noted that the lower the porosity, the smaller the average pore size, the fewer the number of microcracks, the narrower the microcrack width, and the slower the microcrack expansion rate, the better the microstructure.
[0082] Step 4: Screening of recommended trial mix solutions: Based on the evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial mix solutions, screen the recommended trial mix solutions and provide feedback.
[0083] As a preferred option, see Figure 3 As shown, the specific analysis process of step 4 is: compare the evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial matching schemes with the expected values of the evaluation coefficients of workability, mechanical properties, durability, and microstructure of the preset trial matching schemes, and obtain the relative deviations of the evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial matching schemes, which are respectively recorded as .
[0084] By analyzing the formula Get the recommended coefficients for various trial solutions , compare the recommended coefficients of various trial matching schemes with each other, and record the trial matching scheme corresponding to the maximum recommended coefficient as the recommended trial matching scheme.
[0085] It should be noted that the expected values of the evaluation coefficients of workability, mechanical properties, durability, and microstructure are set according to actual application requirements.
[0086] It should be noted that the relative deviation of the evaluation coefficient refers to the absolute value of the difference between the evaluation coefficient and the expected value of the evaluation coefficient.
[0087] In this embodiment, the present invention evaluates the recommended trial mix of cement-based composite materials based on multiple indicators in multiple dimensions of workability, mechanical properties, durability, and microstructure, thereby improving the reliability of the analysis results of the best mix ratio of cement-based composite materials.
[0088] In this embodiment, the present invention conducts workability tests, mechanical property tests, durability tests, and microstructure analysis tests on production samples corresponding to various trial mixing schemes of cement-based composite materials, and conducts a comprehensive reliability evaluation of various trial mixing schemes, which is conducive to better screening out the optimal ratio of cement-based composite materials.
[0089] Step 5. Analysis of the relationship between mix ratio and performance: Analyze the relationship model between the workability, mechanical properties, durability, microstructure and water-cement ratio, cementitious material-aggregate ratio, and fiber-matrix ratio of cement-based composite materials, and provide feedback.
[0090] As a preferred solution, the specific analysis process of step five is as follows: S1: obtaining the water-binder ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix corresponding to various trial mixing schemes of cement-based composite materials, selecting various trial mixing schemes with different water-binder ratios but the same ratio of cementitious material to aggregate and the same ratio of fiber to matrix, recording them as various trial mixing schemes to be analyzed, and sorting the various trial mixing schemes to be analyzed in order of water-binder ratio from small to large.
[0091] Obtain the evaluation coefficients of workability, mechanical properties, durability, and microstructure of each trial mix to be analyzed.
[0092] S2: Based on the single variable principle, according to the water-binder ratio and workability evaluation coefficient corresponding to each trial mix to be analyzed, a trend curve of the workability evaluation coefficient with the increase of water-binder ratio is drawn to obtain the relationship model between the workability and water-binder ratio of cement-based composite materials.
[0093] It should be noted that the specific method for drawing the trend curve of the workability evaluation coefficient as the water-cement ratio increases is as follows: a coordinate system is established with the water-cement ratio as the independent variable and the workability evaluation coefficient as the dependent variable, and the corresponding data points are marked in the coordinate system according to the water-cement ratio and workability evaluation coefficient corresponding to each trial mix to be analyzed. The mathematical model establishment method is used to draw the trend curve of the workability evaluation coefficient as the water-cement ratio increases.
[0094] S3: Similarly, according to the analysis method of S2, the relationship model between the mechanical properties of cement-based composite materials and the water-binder ratio, the relationship model between durability and the water-binder ratio, and the relationship model between microstructure and the water-binder ratio are obtained.
[0095] S4: Similarly, according to the analysis methods of S1-S3, the relationship model between the workability, mechanical properties, durability, microstructure and the ratio of cementitious materials to aggregates, and the ratio of fibers to matrix of cement-based composite materials is obtained.
[0096] In this embodiment, the present invention analyzes the relationship model between the workability, mechanical properties, durability, microstructure and water-cement ratio, cementitious material and aggregate ratio, and fiber and matrix ratio of cement-based composite materials, which is conducive to the subsequent targeted optimization of the proportion of cement-based composite materials.
[0097] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the present invention, they shall all fall within the protection scope of the present invention.
Claims
1. A method for designing the proportion of ultra-high toughness cement-based composite materials and analyzing their performance, characterized in that: The steps include: Step 1: Obtain the preliminary ratio range: Obtain the engineering requirement information of the target project, where the engineering requirement information includes strength grade, durability requirement information, workability requirement information, and special performance requirement information, and analyze the preliminary ratio range of water-binder ratio, cementitious material-aggregate ratio, and fiber-matrix ratio in cement-based composite materials; Step 2, designing a trial mix scheme: according to the preliminary ratio range of the water-binder ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in the cement-based composite material, adjusting and setting the values of the water-binder ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in the cement-based composite material, and obtaining various trial mix schemes of the cement-based composite material; Step 3, performance test of trial mix scheme: obtain various cement-based composite material samples of various trial mix schemes of cement-based composite materials, record them as various samples of various trial mix schemes, conduct workability test, mechanical property test, durability test, microstructure analysis test on each sample of various trial mix schemes, and analyze the evaluation coefficients of workability, mechanical property, durability, and microstructure of various trial mix schemes; Step 4: Screening of recommended trial solutions: Screen the recommended trial solutions based on the evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial solutions, and provide feedback; Step 5. Analysis of the relationship between mix ratio and performance: Analyze the relationship model between the workability, mechanical properties, durability, microstructure and water-cement ratio, cementitious material-aggregate ratio, and fiber-matrix ratio of cement-based composite materials, and provide feedback.
2. The method for designing the proportion of ultra-high toughness cement-based composite materials and analyzing their performance according to claim 1, characterized in that: The specific analysis process of step 1 includes: Obtain the engineering requirement information of the target project, obtain the strength grade, durability requirement information, workability requirement information, and special performance requirement information of the target project, and further obtain the values of various indicators of durability requirement, workability requirement, and special performance requirement of the target project, which are recorded as , Indicates durability requirements The number of the indicator, , Indicates work requirements The number of the indicator, , Indicates special performance requirements The number of the indicator, ; Extract the water-binder ratio, cementitious material-aggregate ratio, fiber-matrix ratio of cement-based composite materials under various engineering conditions stored in the database and the engineering requirements corresponding to various engineering conditions; According to the engineering requirement information corresponding to various engineering conditions, the strength grades corresponding to various engineering conditions and the values of various indicators of durability requirements, workability requirements, and special performance requirements are obtained, and the values of various indicators of durability requirements, workability requirements, and special performance requirements corresponding to various engineering conditions are recorded as , Indicates The number of the engineering condition, .
3. The method for designing proportions and analyzing properties of ultra-high toughness cement-based composite materials according to claim 2, characterized in that: The specific analysis process of step one also includes: Set the strength level matching factors corresponding to the same and different strength levels respectively, compare the strength levels corresponding to various engineering conditions with the strength level of the target project, and obtain the strength level matching factors of various engineering conditions and the target project, which are recorded as ; The values of the durability requirements, workability requirements, and special performance requirements corresponding to various engineering conditions are compared with the values of the durability requirements, workability requirements, and special performance requirements of the target project, and the deviations of the durability requirements, workability requirements, and special performance requirements between various engineering conditions and the target project are obtained, which are recorded as ; By analyzing the formula Obtain the durability matching factor between various engineering conditions and the target project , Indicates the number of engineering conditions; Similarly, according to the analysis method of durability matching factors between various engineering conditions and target projects, the workability matching factors and special performance matching factors between various engineering conditions and target projects are obtained and recorded as ; By analyzing the formula Get the matching index of various engineering conditions and target engineering ,in Indicates the correction factor of the preset fit index, represents a natural constant; The matching indexes of various engineering conditions and the target project are compared with each other, and the engineering conditions corresponding to the maximum matching index are recorded as similar engineering conditions. The ratio ranges of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials under similar engineering conditions are obtained and recorded as the preliminary ratio ranges of water-binder ratio, cementitious material to aggregate ratio, and fiber to matrix ratio in cement-based composite materials.
4. The method for designing proportions and analyzing properties of ultra-high toughness cement-based composite materials according to claim 1, characterized in that: The specific analysis process of step 2 is as follows: According to the preliminary ratio ranges of the water-binder ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in the cement-based composite material, various values are selected in the preliminary ratio ranges of the water-binder ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in the cement-based composite material according to the preset equal interval principle to obtain various reference values of the water-binder ratio, the ratio of cementitious material to aggregate, and the ratio of fiber to matrix in the cement-based composite material; According to the preset principles, various reference values of water-cement ratio, various reference values of cementitious material-aggregate ratio, and various reference values of fiber-matrix ratio in cement-based composite materials are combined to obtain various trial mixing schemes of cement-based composite materials.
5. The method for designing proportions and analyzing properties of ultra-high toughness cement-based composite materials according to claim 1, characterized in that: The specific analysis process of step three includes: A set number of samples are drawn from each sample of various trial mixes for workability test, wherein the workability test includes slump test and expansion test, and the slump and expansion of the samples corresponding to various trial mixes are obtained and recorded as , Indicates The number of the trial combination, ; By analyzing the formula Obtain the workability evaluation coefficients of various trial solutions ,in Represents the correction factor of the preset workability evaluation coefficient, Respectively represent the preset slump and spread thresholds, Respectively represent the weights of the preset slump and spread, .
6. The method for designing the proportion of ultra-high toughness cement-based composite materials and analyzing their performance according to claim 5, characterized in that: The specific analysis process of step three also includes: A set number of samples are selected from each sample of various trial mix schemes for mechanical property tests, wherein the mechanical property tests include compressive strength test, tensile strength test, and flexural strength test. The compressive strength, tensile strength, and flexural strength of the samples corresponding to various trial mix schemes under the set load are obtained and recorded as ; By analyzing the formula Obtain the mechanical properties evaluation coefficients of various trial matching schemes ,in Indicates the correction factor of the preset mechanical property evaluation coefficient, Respectively represent the preset thresholds of compressive strength, tensile strength, and flexural strength, Respectively represent the weights of the preset compressive strength, tensile strength, and flexural strength, .
7. The method for designing the proportion of ultra-high toughness cement-based composite materials and analyzing their performance according to claim 5, characterized in that: The specific analysis process of step three also includes: A set number of samples are selected from each sample of various trial mixing schemes for durability test, wherein the durability test includes impermeability test and frost resistance test, and the impermeability coefficient and frost resistance coefficient of the samples corresponding to various trial mixing schemes under the set test conditions are obtained and recorded as ; By analyzing the formula Obtain the durability evaluation coefficient of various trial solutions ,in Indicates the correction factor of the preset durability evaluation coefficient, Respectively represent the thresholds of the preset anti-permeability coefficient and anti-freezing coefficient, Respectively represent the weights of the preset anti-permeability coefficient and anti-freezing coefficient, .
8. The method for designing proportions and analyzing properties of ultra-high toughness cement-based composite materials according to claim 5, characterized in that: The specific analysis process of step three also includes: A set number of samples are extracted from each sample of various trial mixing schemes for microstructure analysis test to obtain the pore structure information and microcrack information of the samples corresponding to various trial mixing schemes, wherein the pore structure information includes porosity and average pore size, and the microcrack information includes the number of microcracks, the width of microcracks, and the growth rate of microcracks. The porosity, average pore size, number of microcracks, width of microcracks, and growth rate of microcracks of the samples corresponding to various trial mixing schemes are recorded as ; By analyzing the formula Get the microstructure evaluation coefficient of various trial solutions ,in represents the correction factor of the preset microstructure evaluation coefficient, They respectively represent the preset thresholds of porosity, average pore size, number of microcracks, width of microcracks, and microcrack expansion speed.
9. The method for designing the proportion of ultra-high toughness cement-based composite materials and analyzing their performance according to claim 5, characterized in that: The specific analysis process of step 4 is as follows: The evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial solutions are compared with the expected values of the preset evaluation coefficients of workability, mechanical properties, durability, and microstructure to obtain the relative deviations of the evaluation coefficients of workability, mechanical properties, durability, and microstructure of various trial solutions, which are recorded as ; By analyzing the formula Get the recommended coefficients for various trial solutions , compare the recommended coefficients of various trial matching schemes with each other, and record the trial matching scheme corresponding to the maximum recommended coefficient as the recommended trial matching scheme.
10. The method for designing proportions and analyzing properties of ultra-high toughness cement-based composite materials according to claim 1, characterized in that: The specific analysis process of step five is as follows: S1: Obtain the water-binder ratio, cementitious material-aggregate ratio, and fiber-matrix ratio corresponding to various trial mixes of cement-based composite materials, select various trial mixes with different water-binder ratios but the same cementitious material-aggregate ratio and fiber-matrix ratio, record them as various trial mixes to be analyzed, and sort the various trial mixes to be analyzed in order of water-binder ratio from small to large; Obtain the evaluation coefficients of workability, mechanical properties, durability, and microstructure of each trial mix to be analyzed; S2: Based on the single variable principle, according to the water-binder ratio and workability evaluation coefficient corresponding to each trial mix to be analyzed, a trend curve of the workability evaluation coefficient as the water-binder ratio increases is drawn to obtain the relationship model between the workability and water-binder ratio of cement-based composite materials; S3: Similarly, according to the analysis method of S2, the relationship model between the mechanical properties of cement-based composite materials and the water-binder ratio, the relationship model between durability and the water-binder ratio, and the relationship model between microstructure and the water-binder ratio are obtained; S4: Similarly, according to the analysis methods of S1-S3, the relationship model between the workability, mechanical properties, durability, microstructure and the ratio of cementitious materials to aggregates, and the ratio of fibers to matrix of cement-based composite materials is obtained.
Citation Information
Patent Citations
Design method of hydraulic high-ductility cement-based composite material based on crack width and ultimate elongation control
CN119066860A
Intelligent design method and device for nanometer reinforced cement-based material
CN116486960A
Preparation method of rubber modified ultrahigh-ductility cement-based composite material
CN117003518A
Cited By
Proportioning design method of cement-based rock stratum modified material
CN121938525A